JURIDICAL ANALYSIS OF OUTSOURCED WORKERS BASED ON LAW NUMBER 6 OF 2023 ON STIPULATION OF GOVERNMENT REGULATION IN LIEU OF LAW NUMBER 2 OF 2022 ON JOB CREATION INTO LAW - PRAMANA, NDINTA HERRY; PANJAITAN, HULMAN; BETLEHN, ANDREW (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
This research discusses the juridical analysis of outsourced workers in light of Law No. 6 of 2023 on Job Creation Stipulating Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation into Law. This study aims to determine the regulation of outsourced workers after the issuance of the 2023 Job Creation Law and whether the regulation is able to protect and fulfil the rights of outsourced workers from the exploitation of employers that continues to occur in Indonesia today. This research uses qualitative research with normative legal research methods. The data sources used are primary data in the form of laws and government regulations of the Republic of Indonesia that are currently in force, and secondary data consisting of books, journals and websites. The results of this research can be concluded that in Law Number 13 of 2003 on Manpower, several provisions have been amended by Law Number 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law, including provisions relating to outsourced labour. Based on the old comparison between the Manpower Law and the Job Creation Law, it is worth noting that the Job Creation Law has also caused controversy, especially in relation to labour protection. Some provisions, such as those relating to the type of work, working time, and severance pay, are considered to reduce protection for outsourced labour. In addition, the Job Creation Law No. 6 of 2023 regulates the protection of workers from social security, working days and hours, time and holidays, wages and benefits, and provisions for termination of employment. However, in the event of discrepancies experienced by outsourced workers, they can take non-litigation legal action such as bipartite, mediation, conciliation, or arbitration